Maternal adverse childhood experiences, child mental health, and the mediating effect of maternal depression: A cross-sectional, population-based study in rural, southwestern Uganda - Kim, Andrew Wooyoung; Rieder, Amber D.; Cooper-Vince, Christine E.; Kakuhikire, Bernard; Baguma, Charles; Satinsky, Emily N.; Perkins, Jessica M.; Kiconco, Allen; Namara, Elizabeth B.; Rasmussen, Justin D.; Ashaba, Scholastic; Bangsberg, David R.; et al. (American Journal of Biological Anthropology, 2023)
Objectives: This study aimed to examine the intergenerational effects of maternal adverse childhood experiences (ACEs) and child mental health outcomes in rural Uganda, as well as the potentially mediating role of maternal depression in this pathway. Additionally, we sought to test the extent to which maternal social group membership attenuated the mediating effect of maternal depression on child mental health. Methods: Data come from a population-based cohort of families living in the Nyakabare Parish, a rural district in southwestern Uganda. Between 2016 and 2018, mothers completed surveys about childhood adversity, depressive symptoms, social group membership, and their children's mental health. Survey data were analyzed using causal mediation and moderated-mediation analysis. Results: Among 218 mother–child pairs, 61 mothers (28%) and 47 children (22%) showed symptoms meeting cutoffs for clinically significant psychological distress. In multivariable linear regression models, maternal ACEs had a statistically significant association with severity of child conduct problems, peer problems, and total child difficulty scores. Maternal depression mediated the relationship between maternal ACEs and conduct problems, peer problems, and total difficulty, but this mediating effect was not moderated by maternal group membership. Conclusions: Maternal depression may act as a potential mechanism linking maternal childhood adversity with poor child mental health in the next generation. Within a context of elevated rates of psychiatric morbidity, high prevalence of childhood adversity, and limited healthcare and economic infrastructures across Uganda, these results emphasize the prioritization of social services and mental health resources for rural Ugandan families
Keywords: Adverse childhood experiences; Child mental health; Depression; Mediation analysis; Uganda